A Randomized Controlled Trial of a Home-Based Action Observation Intervention to Improve Walking in Parkinson Disease - Jaywant, Abhishek (Arch Phys Med Rehabil, 2016)
OBJECTIVE: To examine the feasibility and efficacy of a home-based gait observation intervention for improving walking in Parkinson disease (PD). DESIGN: Participants were randomized to an intervention or control condition. A baseline walking assessment, a training period at home, and a post-training assessment were conducted. SETTING: The laboratory and participants' home and community environments. PARTICIPANTS: 23 non-demented individuals with PD experiencing walking difficulty. INTERVENTION: In the Gait Observation (intervention) condition, participants viewed videos of healthy and parkinsonian gait. In the Landscape Observation (control) condition, participants viewed videos of moving water. These tasks were completed daily for eight days. MAIN OUTCOME MEASURES: Spatiotemporal walking variables were assessed using accelerometers in the laboratory (baseline and post-training assessments) and continuously at home during the training period. Variables included daily activity, walking speed, stride length, stride frequency, leg swing time, and gait asymmetry. Questionnaires including the 39-item Parkinson's Disease Questionnaire (PDQ-39) were administered to determine self-reported change in walking, as well as feasibility. RESULTS: At post-training assessment, only the Gait Observation group reported significantly improved mobility (PDQ-39). No improvements were seen in accelerometer-derived walking data. Participants found the at-home training tasks and accelerometer feasible to use. CONCLUSION: Participants found procedures feasible and reported improved mobility, suggesting that observational training holds promise in the rehabilitation of walking in PD. Observational training alone, however, may not be sufficient to enhance walking in PD. A more challenging and adaptive task, and the use of explicit perceptual learning and practice of actions, may be required to effect change.